Optimizing School Financial Management: The Role of Financial Information Systems in Education - Andika Isma; Nurul Aditya Pratiwi; Miftahul Janna Awaliyah; Roman Febrian Dasmasela; Aprilia Manda Putri (Program Studi Teknik Komputer, 2024)
In today's digital era this, System Financial Information (GIS) has become element crucial in management finance institution education, especially in the environment school. SIK no only works as a digital platform, but also as very important tool for students, parents, and staff school in management finance as well as transaction other. Implementation of SIK in the environment school No only simply step technological, but rather a strategy that can increase level transparency in management finances, reduce burden administration, and help school in optimizing income as well as reduce costs are not need. The existence of SIK becomes key in presenting efficiency and accuracy in the management process finance school. With reduce potency error or obscurity in management finance, SIK has role strategic in prevent and overcome potency problem serious that can be bother performance school in a way comprehensive. Apart from that , the application of SIK is also open opportunity For increase quality education provided to students, because source power and funds available allocated with more effective.